2018
DOI: 10.4172/2155-9546.1000526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Catfish Pituitary Gland Extract Dosages on Eggs and Hatchlings Quantity of African Catfish, Clarias gariepinus at a Constant Latency Period

Abstract: An experiment was conducted to assess the effects of different dosages of catfish pituitary glands extract (CPGE) on eggs and hatchlings quantity of African catfish, Clarias gariepinus at a constant latency period. In this experiment, four dosages (2 mg/kg, 3 mg/kg, 4 mg/kg and 5 mg/kg of female) were used. Each dosage extracted from a male (300 g to 305 g) was injected to individual female (350 g to 355 g) at three replications and a total of 12 females were injected. The females were striped after 17 hour at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Both dosages used from the present study provided similar result in terms of egg quantity; however, lower dosage demonstrates advantage in terms of the number of breeders it can cater since utilisation of 4 mg kg -1 body weight is already adequate to induce the spawning of African catfish in contrast to higher dosage (200 mg kg -1 body weight). This result agreed with the findings of Mosha and Mlingi (2018) that exact dosage of 4 mg kg -1 body weight gave the highest eggs spawned for African catfish using homoplastic pituitary extract compared to those dosages that are lower or higher than 4 mg kg -1 body weight. Further, Michael et al (2004) reported that high dosage application in inducing Eleutherodactylus conqui to spawn using different hormone mixtures resulted to onset occurrence of side effects to breeders such as hemorrhaging, ataxia and lethargy which compromised egg quality and quantity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both dosages used from the present study provided similar result in terms of egg quantity; however, lower dosage demonstrates advantage in terms of the number of breeders it can cater since utilisation of 4 mg kg -1 body weight is already adequate to induce the spawning of African catfish in contrast to higher dosage (200 mg kg -1 body weight). This result agreed with the findings of Mosha and Mlingi (2018) that exact dosage of 4 mg kg -1 body weight gave the highest eggs spawned for African catfish using homoplastic pituitary extract compared to those dosages that are lower or higher than 4 mg kg -1 body weight. Further, Michael et al (2004) reported that high dosage application in inducing Eleutherodactylus conqui to spawn using different hormone mixtures resulted to onset occurrence of side effects to breeders such as hemorrhaging, ataxia and lethargy which compromised egg quality and quantity.…”
Section: Discussionsupporting
confidence: 91%
“…African catfish, goat and pig. Pituitary extract form African catfish at 4 mg kg -1 body weight served as the control treatment (Mosha and Mlingi 2018). Additionally, the dosages of both 4 mg kg -1 and 200 mg kg -1 body weight from goat and pig pituitary extracts were used as the other treatments.…”
Section: Pituitary Extract Preparation and Injectionmentioning
confidence: 99%
“…Most fish farmers have to obtain their seeds from wild capture, mainly from rivers. This is due to the constraints that, there are few number of operating hatcheries, low level of technology in larval rearing and live feeds production [33].…”
Section: Unreliable Seed Supplymentioning
confidence: 99%
“…Its reproduction is seasonal and influenced by water temperature, photoperiod, and water level [3][4][5]. Extenders are important for inducing reproduction, and the pituitary gland is the main source of hormones responsible for reproduction in animals [6][7].…”
Section: Introductionmentioning
confidence: 99%